The thymic apparatus - Machado, Deolindo (Revista de la Universidad Nacional de Córdoba, 1942)
In man, the thymic apparatus is a voluminous organ, composed of a series of solid lobes as a whole. In amphibians and lower fish, there are seven or eight thymuses on each side of the body, forming the so-called thymic apparatus. The thymus could be said to be a transitory organ and is little known, and is complicated and variable in the same species of animal. Hence the need for its organogenesis and the study of the comparative histology of this apparatus.